Targeting DNA repair in gliomas. Issue 6 (December 2019) - Beckta, Jason M.; Bindra, Ranjit S.; Chalmers, Anthony J.
Abstract : Purpose of review: Gliomas represent a disparate group of malignancies with varying clinical outcomes despite a tremendous amount of time, effort, and resources dedicated to their management and understanding. The most aggressive entity, glioblastoma, has a dismal prognosis with poor local control despite intense local and systemic treatment, including radiation therapy. Recent findings: Given the heterogeneity in genotype, phenotype, and patient outcomes, researchers and clinicians have turned their attention toward attacking DNA damage response and repair mechanisms in gliomas in an effort to develop novel chemo and radiosensitizers. However, despite extensive work in both the laboratory and the clinic, no sensitizers have yet to emerge as clear options in the treatment of glioma, often because of meager preclinical data or an inability to penetrate the blood–brain barrier. Summary: This review will examine current understanding of molecular DNA repair targets in glioma and their potential exploitation to improve local control and, ultimately, overall survival of patients afflicted with these diseases.